2008
DOI: 10.1016/j.leaqua.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level analysis of team climate and interpersonal exchange relationships at work

Abstract: This paper seeks to advance research on interpersonal exchange relationships between supervisors, subordinates, and coworkers at work by integrating social exchange, workplace friendship, and climate research to develop a multi-level model. We tested the model using hierarchical linear modeling (HLM) with data obtained from a sample of 215 manager-employee dyads working in 36 teams. At the individual level, leader-member exchange (LMX) was found to be related to workplace friendship. Further, workplace friends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(194 citation statements)
references
References 61 publications
6
175
0
5
Order By: Relevance
“…While all predictors were measured based on a 5-point Likert scale response, the criteria variables (group members' innovation) were measured based on a "yes" or "no" response. We aggregated constructive culture and knowledge management as a group-level variable, which helped reduce the potential for spurious results based on individual-level observed variance (Tse, Dasborough, & Ashkanasy, 2008). In addition, we also conducted EFA by including all items from all of the constructs in this study into an analysis and found seven factors emerging.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…While all predictors were measured based on a 5-point Likert scale response, the criteria variables (group members' innovation) were measured based on a "yes" or "no" response. We aggregated constructive culture and knowledge management as a group-level variable, which helped reduce the potential for spurious results based on individual-level observed variance (Tse, Dasborough, & Ashkanasy, 2008). In addition, we also conducted EFA by including all items from all of the constructs in this study into an analysis and found seven factors emerging.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Although some workplace friendships can have adverse effects (see Litwin and Hallstein 2007), empirical research suggests that co-worker friendships can have favourable outcomes for both employees and organizations (Berman et al 2002;Sias 2005;Tse et al 2008). In a study comparing team processes of co-workers who were friends and co-workers who were acquaintances, Jehn and Shah (1997) found that friendship teams generally were more communicative, cooperative, and encouraging than acquaintance teams.…”
Section: Team Contextmentioning
confidence: 99%
“…The latter has been referred to as team-member exchange (TMX). In a comprehensive qualitative and quantitative study, Tse & Dasborough (2008) [131] have explained the development of team member relationships in terms of…”
Section: Major Theoretical Contributions In Developing the Phenomenamentioning
confidence: 99%
“…Team-member affect is mainly specified in a team context and can be defined as an individual team member"s own affect in relation to their team member exchanges. In a team context, emotional responses of team members reflect the current interactions between team members, which will pave the way for future team member relationship development (Tse & Dasborough, 2008) [131]. Positive affect is associated with increased team member commitment and satisfaction.…”
Section: Team-member Affectmentioning
confidence: 99%
See 1 more Smart Citation